Roughness characterisation of gas phase micromachining process suitable for fabricating silicon based microsystems. (20th April 2005) - Packirisamy, M.; Stiharu, I.; Flores, L.
Non-conventional or advanced machining techniques are becoming the enabling fabrication techniques for many emerging fields including Micro Electro Mechanical Systems (MEMS) or Microsystems Technology (MST). The processes used for MEMS fabrication include standard semiconductor fabrication processes and emerging micromachining techniques. Among the challenges emerging from the manufacturing of MEMS devices, post-processing seems to be one of the most sensitive issues. The non-traditional common post-processing techniques are bulk micromachining and surface micromachining. It has been a challenge for MEMS designers to develop a micromachining technique that is compatible with IC (Integrated Circuits) processes and also capable of making MEMS structures through both bulk and surface micromachining with acceptable surface roughness requirements. The selected micromachining process should not affect the integrity of the free standing structure due to the reduced selectivity and aggressive etch of the adjacent electronic circuitry. Moreover, the integrity of the released structure, the dynamic properties as well as the electrostatic characteristics, are strongly dependent on the achieved roughness of the surfaces produced by the etching process. Hence, this paper presents the surface roughness characterisation of gas phase micromachining with XeF2 that is suitable for fabricating integrated MEMS with both micromechanical and microelectronics components. This paper also presents some fabricated microsystems using this process.